Application of the Kamal-He’s Iterative Method to Klein-Gordons Equations - Adejoh Jeremiah; M. Y. Adamu; A. G. Madaki; Okai J. O; Michael Cornelius (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
This study demonstrates the effectiveness and accuracy of the KHM for solving both linear and nonlinear Klein-Gordon equations. Through graphical comparisons with other methods such as VIM, TAM, and NIM, and error analysis, the results confirm the high precision and reliability of KHM. The approach is shown to be straightforward, easy to implement, and highly efficient for solving linear PDEs. Additionally, KHM provides the exact solution for nonlinear Klein-Gordon equations in a single iteration, highlighting its computational efficiency. Overall, the KHM is proven to be a powerful and reliable tool for solving a wide range of equations in mathematical physics.